ANTIOXIDANT ACTIVITY OF THREE ECOTYPES OF MACA (LEPIDIUM MEYENII WALP) TREATED WITH GAMMA RADIATION - Carrión, J. (2009)
Various doses (0-20 kGy) of gamma radiation have been applied to samples of maca (Lepidium meyenii walp) flour, yellow, white and purple ecotypes, to decontaminate them. The gamma radiation dose required to eliminate the aerobic mesophiles was 12-15 kGy while it was necessary to applied 1-8 kGy to kill fungi, depending on the ecotype of Maca. We have determined the antioxidant activity of the irradiated samples by the method of neutralization of DPPH radical. IC50 values of the studied samples indicate that gamma radiation does not substantially alter the antioxidant activity of aqueous extracts of maca yellow, white and purple. In contrast, the antioxidant activity of hydroalcoholic extracts of irradiated maca yellow decrease sharply, but not the other ecotypes.